Wind power costs in Portugal - Saleiro, Carla (2007)
In a way to reduce the external energy dependence, increasing also the investments in renewable energy sources and aiming for the concretization of the European renewable objectives, the Portuguese government defined a goal of 5100 MW of installed wind power, up to 2012. If the drawn objectives are accomplished, by 2010 the wind power share may reach values comparable to leading countries like Denmark, Germany or Spain. The Portuguese forecasts also indicate a reinforcement of the natural gas fired generation in particular through the use of the combined cycle technology, following the European tendency. This analysis sets out to evaluate the total generating cost of wind power and CCGT in Portugal. A life cycle cost analysis was conducted, including investment costs, O&M costs, fuel costs and external costs of emissions, for each type of technology. For the evaluation of the externalities ExternE values were used. The results show that presently the wind power production cost is higher than the CCGT one, at least from the strictly financial point of view. CCGT costs increase significantly when charges for externalities are included. However, they only reach levels higher than the equivalents for wind power for high externality costs estimations. This partially results from the low load factor of the wind farms in Portugal and also from the lowemission levels of the gas fired technology used in the comparison. A sensitive analysis of the technical and economical parameters was also conducted. Particular attention was given to the natural gas prices due to the possible increase over time. The fuel escalation rate is the parameter that has larger effects on the final costs. It was verified that the total cost of wind plant is more influenced by the load factor than the total cost of CCGT.